2010
DOI: 10.4088/jcp.08m04673yel
|View full text |Cite
|
Sign up to set email alerts
|

Lithium Treatment Effects on the Neuropsychological Functioning of Patients With Bipolar I Disorder

Abstract: Patients with bipolar I disorder have verbal memory deficits that are not explained by medication or by lithium monotherapy, but by the condition itself.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
41
0
4

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(45 citation statements)
references
References 29 publications
0
41
0
4
Order By: Relevance
“…Literature regarding the neurocognitive effects of psychotropic medication is mixed; some studies claim that deficits are due to medication, specifically when patients are taking lithium [70]. Other medications such as risperidone and quietapine may lead to drowsiness and this may be confounded with neuropsychological deficits associated with BD too [71].…”
Section: Discussionmentioning
confidence: 98%
“…Literature regarding the neurocognitive effects of psychotropic medication is mixed; some studies claim that deficits are due to medication, specifically when patients are taking lithium [70]. Other medications such as risperidone and quietapine may lead to drowsiness and this may be confounded with neuropsychological deficits associated with BD too [71].…”
Section: Discussionmentioning
confidence: 98%
“…On the other hand, bipolar patients medicated with lithium (N=20) did not differ from those who were unmedicated (N=20) in terms of their cognitive performance 32 . This was an uncontrolled, open study; it is unclear how the patients were assigned to their treatment groups.…”
Section: Potencial Deleterious Effects Of Medication On Cognition In mentioning
confidence: 98%
“…28 Although patients on lithium frequently complain of cognitive impairment, prescribing clinicians should be aware that the cognitive deficits in BD patients can, in part, be a manifestation of the disease itself rather than an adverse effect of lithium. 29 A meta-analysis of 12 studies with lithium treatment concluded that lithium's adverse effect on memory is present but limited. 30 Similarly, a prospective study conducted with 44 euthymic patients with bipolar I disorder suggested no significant difference in neurocognitive performance in patients prescribed bipolar medications in comparison to unmedicated patients.…”
Section: Cognitive Impairmentmentioning
confidence: 99%